2019
DOI: 10.1590/1806-93042019000300012
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight and the delay on the eruption of deciduous teething in children

Abstract: Objectives: To analyze the association between low birth weight (LBW) and the occurrence of the delay on the eruption of deciduous teething (DEDT) in children from 04 to 30 months, living in Salvador, Bahia. Methods: A cross-sectional study involved 520 children at four to thirty months of age, from public, private and philanthropic daycares from two districts in Salvador. A descriptive analysis and unconditional logistic regression were done to estimate the odds ratios (ORs), using the Confidence Interval of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The authors presumed that LBW may contribute to delayed teething because nutritional factors influence odontogenesis and teeth eruption. 21 Our results that infants with NBW were at a greater risk for ECC than those with LBW may be attributable to the delayed teething caused by LBW and the consequent delay in intraoral exposure. Moreover, a systematic review of studies on the relation of ECC and body mass index as an indicator of the body weight status reported that overweight children were at a higher risk for ECC than normal weight/underweight children, which supports our results that ECC is less likely to occur among LBW infants than among NBW infants.…”
Section: Discussionmentioning
confidence: 62%
“…The authors presumed that LBW may contribute to delayed teething because nutritional factors influence odontogenesis and teeth eruption. 21 Our results that infants with NBW were at a greater risk for ECC than those with LBW may be attributable to the delayed teething caused by LBW and the consequent delay in intraoral exposure. Moreover, a systematic review of studies on the relation of ECC and body mass index as an indicator of the body weight status reported that overweight children were at a higher risk for ECC than normal weight/underweight children, which supports our results that ECC is less likely to occur among LBW infants than among NBW infants.…”
Section: Discussionmentioning
confidence: 62%
“… 10 - 25 Although the association between permanent tooth eruption (or delayed exfoliation of the primary tooth) was previously investigated in other Brazilian populations, 19 , 20 we also decided to explore the impact of the nutritional status on tooth eruption time in School children from Alfenas, which is a medium size city located in Minas Gerais state. It is important to emphasize that Brazil is a country with a continental size with a different ethnic composition ranging according to the state, 2 as well as socioeconomic and cultural differences. The influence of ethnicity 8 and socioeconomic aspects 9 on tooth eruption have already been documented and suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors could affect primary and permanent tooth eruption. Some studies suggested that low birth weight and prematurity, 1 - 4 endocrinology conditions, 5 - 7 ethnicity, 8 socioeconomic aspects, 9 and nutritional status, such as malnourishment (underweight), and obesity, 7 , 10 - 25 could affect tooth eruption leading to a delay or earlier tooth eruption and primary tooth exfoliation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the eruption timing of primary teeth is genetically determined. However, perinatal maternal circumstances, early childhood metabolic, systemic, and nutritional factors, such as the type of feeding, socioeconomic variables, and ethnicity are also all linked to primary tooth eruptive timing [ 2 , 3 , 5 , 6 , 7 , 8 , 9 ]. The effect of gender differences on the eruption times of primary teeth has not been clearly determined.…”
Section: Introductionmentioning
confidence: 99%
“…Birth weight is an indicator of perinatal factors, and it has been reported in the literature that birth weight is associated with age at the eruption of primary teeth [ 2 , 4 , 12 ]. There is a positive correlation between late eruption and low birth weight due to the general developmental delay in these children [ 9 ]. This supports the assumption that malnourished children in the prenatal period, when teeth are just beginning to form, suffer from nutritional problems that can negatively impact the development of their primary teeth [ 1 , 9 ].…”
Section: Introductionmentioning
confidence: 99%